PERAN PERILAKU KERJA INOVATIF DALAM MEMEDIASI PENGARUH PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Pada Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Purworejo) - Ika Sabila Nur Aini,; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The purpose of this study was to determine the effect of variables of Perceived Organizational Support, Innovative Work Behavior on improving Job Performance. Based on company data, it is shown that there was a decline in job performance in 2021. The phenomenon of decreasing performance is what underlies this research. Then build an empirical research model Perceived Organizational Suppor on Job Performance at Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Purworejo through the concept of Innovative Work Behavior. The data used in this study are primary data in the form of distributing questionnaires as many as 42 employee respondents in all departments at Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Purworejo. The technique used in this study was census method, all populations in this study were used as respondents. The test of this study used path analysis and to test the effect of intervening variables, the specific indirect effect test was used. The statistical method used is Partial Least Square (PLS). Processing data of this research using SmartPLS version 3.2.9 software. The results showed that (1) of Perceived Organizational Support is positive and significant to the improving Job Performance. (2) Perceived Organizational Support is positive and significant to the Innovative Work Behavior. (3) Innovative Work Behavior has a positive and insignificant effect on Job Performance. From the results of the intervening test on the specific indirect effect, Innovative Work Behavior can be an intervening variable between Perceived Organizational Support to Job Performance. This means that the organizational support felt by employees is able to guide employees to continue to develop at work so that they have innovative and insightful behavior to improve their capabiliti